Barongan and Jaranan Art Performance As A Form of Cultural Heritage Preservation In Kebumen Village - Ardiyanti, Rizqi Meila; Hafidzah, Ibna Azka (JGEN : Jurnal Pengabdian Kepada Masyarakat, 2024)
As the times develop, local culture experiences contact with foreign cultures. Young people are more interested in following foreign cultures that are considered to keep up with the times and forget about local culture. This is a challenge for every culture because of the lack of the next generation to learn and practice its culture. The role of students in service is also to preserve the existing culture, so this paper aims to explain the performance of barongan and jaranan arts in Kebumen Village as a form of cultural preservation. The methods used are field and observation. The result of this study is that in order to preserve the culture owned, the Kebumen Village cultural association held a barongan and jaranan art performance in collaboration with other village cultural associations, where children in the village were included in displaying the art of barongan and jaranan.